Economic Simulation of Central Java: Indonesia’s Province-Based IRIO Analysis - Firmansyah, Firmansyah; Azyzia, Siti Hilmiati; Prayudya, Daffa Rizqi (Economics Development Analysis Journal, 2024)
This study simulates increased sectoral investment in the economy of Central Java Province, Indonesia. Using output and household income indicators, several policy scenarios are applied to Indonesia's interregional input-output (IRIO) tables, including green economic scenarios. The aim of this research is to identify the most impactful policy on the economy of Central Java based on the results of investment policy simulations. Investment injections are conducted in production sectors within Central Java and in sectors outside the province. By assessing the direct, indirect and induced effects on economic sectors and households, cross-sectoral insights for regional development policies, the simulation results show that the Central Java economy experiences the best impact in terms of sectoral household output and income levels. In IRIO analysis, this impact is seen as a multiplier effect from sectors within and beyond Central Java. The findings imply that policies focused on local sector development will generate the highest income levels and largest output multiplier for Central Java given the existing economic conditions, while green economic policies do not have insignificant economic impacts compared to non-green policies. It is crucial to develop additional policy scenarios targeting both local and non-local industries to obtain more sensitive simulation results.